Production performance, breeding practices and challenges of Holstein-Local crossbred cattle in some selected areas of Bangladesh (Bangladesh Journal of Animal Science, 2023)
The aim of this study was to investigate productive and reproductive performances, current cattle breeding practices and its associated problems in different Holstein-Local (HF×L) crossbred genotypes under existing management condition of Bangladesh. Data on HF×L crossbred dairy cows were collected from the selected farmers of Natore, Sirajganj, Kishoreganj, Tangail and Gazipur districts while breeding bulls’ information were collected from different cattle breeding service providers. Genotype had significant effects on weight at first heat (WFH), mature body weight (MBW), age at first heat (AFH), age at first calving (AFC), post-partum heat period (PPHP), daily milk yield (DMY) and peak milk yield (PMY) (PHF75%×L